2015
DOI: 10.1117/12.2181384
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hidden diffuse surfaces using phase-shifting endoscopic digital speckle pattern interferometry

Abstract: Digital speckle pattern interferometry (DSPI) is an important optical tool which is widely used in many sophisticated applications. However, a traditional DSPI system can only be used to investigate the outer surfaces which can be easily observed. Therefore, an endoscopic DSPI was proposed to detect the internal and hidden surfaces. It has a rigid or flexible endoscopic tube to allow a hidden surface being clearly imaged. A Fiber-optics-based setup makes the proposed DSPI system compact and robust. The tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…To further enhance the flexibility and make the measurement of hidden structures possible, the combination of optical metrology and endoscopy was introduced [265,266]. Gao et al [267] proposed a phase-shifting endoscopic ESPI system for the measurement of cavities with a small access aperture. A combination of a pulsed holographic interferometric system and endoscopes was reported [18], and the adoption of optical fibers makes it more flexible so that it can be applied under industrial operations and harsh environments, as shown in figure 26.…”
Section: Cooperative Integrationmentioning
confidence: 99%
“…To further enhance the flexibility and make the measurement of hidden structures possible, the combination of optical metrology and endoscopy was introduced [265,266]. Gao et al [267] proposed a phase-shifting endoscopic ESPI system for the measurement of cavities with a small access aperture. A combination of a pulsed holographic interferometric system and endoscopes was reported [18], and the adoption of optical fibers makes it more flexible so that it can be applied under industrial operations and harsh environments, as shown in figure 26.…”
Section: Cooperative Integrationmentioning
confidence: 99%